THE IMPACT OF INFRASTRUCTURE ON RURAL ECONOMIC GROWTH: A COMPREHENSIVE LITERATURE REVIEW - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
This study examines the impact of infrastructure on economic growth in rural areas through a comprehensive literature review. Good infrastructure, including roads, bridges, clean water supply, and electricity, is proven to play an important role in promoting economic growth. Improved access and connectivity brought about by infrastructure development facilitate the distribution of goods and services, reduce transport costs, and expand access to markets. This not only increases the productivity of the agricultural sector and small and medium enterprises, but also opens up opportunities for economic diversification and attracts investment. In addition, adequate infrastructure contributes to improvements in the social aspects and welfare of rural communities. Public facilities such as schools, clinics and access to information technology improve people's quality of life, providing greater opportunities for better education and health services. As such, these improvements in the quality of human capital strengthen the foundation for long-term inclusive and sustainable economic growth. The study emphasises the importance of consistent investment in infrastructure development to achieve this goal.